2018
DOI: 10.1074/jbc.r117.804641
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and post-transcriptional regulation of autophagy in the yeast Saccharomyces cerevisiae

Abstract: Autophagy is a highly conserved catabolic pathway that is vital for development, cell survival and the degradation of dysfunctional organelles and potentially toxic aggregates. Dysregulation of autophagy is associated with cancer, neurodegeneration and lysosomal storage diseases. Accordingly, autophagy is precisely regulated at multiple levels (transcriptional, post-transcriptional, translational and post-translational) to prevent aberrant activity. Various model organisms are used to study autophagy but the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 100 publications
0
50
0
Order By: Relevance
“…This process continued until the vacuole filled such cells, while their fluorescence and then their nucleus completely vanished. These features suggest that some cells might attempt surviving by autophagy ( 50 , 51 ), until they succumb to cell death. Taken together with the stable bimodal gene expression histograms for cooled and heated NF0 cells, we concluded that cooled and heated yeast cells segregate into two phenotypically distinct subpopulations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This process continued until the vacuole filled such cells, while their fluorescence and then their nucleus completely vanished. These features suggest that some cells might attempt surviving by autophagy ( 50 , 51 ), until they succumb to cell death. Taken together with the stable bimodal gene expression histograms for cooled and heated NF0 cells, we concluded that cooled and heated yeast cells segregate into two phenotypically distinct subpopulations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The myriad of mechanisms that are exerted by the cell to control the induction and magnitude of the autophagy response, along with the high level of pathway conservation throughout eukaryotes, highlight how important this process is for maintaining cellular integrity and survival during stress. Although here we focus mainly on post‐transcriptional regulation by RNA decay, cells also utilize multiple layers of regulation through transcriptional (Bartholomew et al, ; Bernard, Jin, Gonzalez‐Rodriguez, et al, ; Bernard, Jin, Xu, & Klionsky, ; Jin et al, ), translational (Lubas et al, ; Rojas‐Rios et al, ; Wek, Zhu, & Wek, ) and post‐translational (Feng et al, ; Mao et al, ; Russell et al, ) mechanisms (reviewed in Delorme‐Axford & Klionsky, ; Feng, Yao, & Klionsky, ; Popelka & Klionsky, ). Despite the immense progress that has been achieved towards understanding how cells control autophagy, many questions remain.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast kinase Rim15 positively regulates autophagy through the integration of signals from two major nutrient sensing pathways—TOR and protein kinase A (Delorme‐Axford & Klionsky, ; Reggiori & Klionsky, ; Yorimitsu, Zaman, Broach, & Klionsky, ). Rim15 phosphorylates at least two mediators of ATG gene repression in yeast—Ume6 (Bartholomew et al, ) and Rph1 (Bernard et al, ).…”
Section: Autophagy Regulation By Rna Decaymentioning
confidence: 99%
See 1 more Smart Citation
“…In short, autophagy under normal conditions occurs at a low intensity; however, this process is clearly enhanced as a result of various types of abiotic and biotic stresses mboxciteB29-ijms-741503,B129-ijms-741503,B130-ijms-741503,B131-ijms-741503. In yeast, the main factors that increase the intensity of autophagy are carbon, nitrogen and phosphate starvation [24,129]. In plants, it is known that carbon or nitrogen starvation significantly increases the intensity of autophagy [7,24,29,36,132,133].…”
Section: Regulation Of Autophagic Body Degradationmentioning
confidence: 99%